Analisa Perlindungan Hukum terhadap Anak sebagai Korban Bullying di Sekolah Dasar Batang Arah Tapan - Sari, Neci Rofita; Nuzuli, Ahmad Khairul; Oktaviana, Winda (Lembaga Yasin AlSys, 2023)
There are no written regulations containing prohibitions and threats of criminal The definition of a child according to Law number 23 of 2002 in conjunction with Law Number 35 of 2014 concerning child protection Article 1 paragraph (1) is someone who is not yet 18 (eighteen) years old, including children who are still in the womb. The problem in this research is how is the legal protection of children as victims of bullying at Batang Arah Tapan Elementary School and what factors become obstacles to legal protection of children as victims of bullying at the Batang Arah Tapan Public Elementary School. The type of research used is empirical and the whole is done using qualitative research methods. Batang Arah Tapan Public Elementary School has not maximally provided legal protection for children who are victims of bullying because according to the author's research sanctions against perpetrators of bullying perpetrated by the school. Factors inhibiting legal protection for children who are victims of bullying at public elementary schools in Batang Arah Tapan include the factor of parents who pay less attention to children because they are busy. Apart from that, there is a phenomenon in society that bullying is not considered a serious problem.